2003
DOI: 10.1007/s00431-003-1315-7
|View full text |Cite
|
Sign up to set email alerts
|

Transient exocrine pancreatic insufficiency as a possible complication of an enterovirus infection

Abstract: This is the first description of a child with a transient but severe exocrine pancreatic insufficiency probably induced by an ordinary enterovirus infection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Low FE1 levels were reported in similar scenarios of diffuse small bowel injury from enteric pathogens (23) and many enteropathies (24,25). Transient EPI, as a clinical diagnosis, was reported following enterovirus infections in the pediatric population (26).…”
Section: Discussionmentioning
confidence: 84%
“…Low FE1 levels were reported in similar scenarios of diffuse small bowel injury from enteric pathogens (23) and many enteropathies (24,25). Transient EPI, as a clinical diagnosis, was reported following enterovirus infections in the pediatric population (26).…”
Section: Discussionmentioning
confidence: 84%
“…The concomitant findings of a positive CVB4 IgG titer and persistently low levels of pancreatic enzymes provide stronger evidence of the infection timeline. Enteroviruses, including CVB4, have been established to cause transient exocrine pancreatic insufficiency for longer than 1.5 months [ 12 ]. In this patient, the first laboratory evidence of pancreatic insufficiency was documented at the onset of pleurodynia, providing strong evidence of active CVB4 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although pancreatic insufficiency is usually described as a consequence of chronic pancreatitis, cystic fibrosis, and Shwachman‐Diamond disease (1,2,4), the pancreatic insufficiency in our case series could not be attributed to any of these causes. Van Biervliet et al (8) reported a case of a 9‐year‐old boy who presented with fever, abdominal pain, diarrhea, and vomiting, all symptoms resolved but the diarrhea persisted for a month accompanied by an 8% weight loss. Broad investigation revealed FE1 level of <15 mg/g stool and steatorrhea.…”
Section: Discussionmentioning
confidence: 99%
“…only 1 case report that described severe pancreatic insufficiency after gastrointestinal infection with enterovirus (8).…”
Section: What Is Newmentioning
confidence: 99%
See 1 more Smart Citation